Peranan Kementerian Hukum dan Hak Asasi Manusia dalam Tata Kelola Kolaboratif Pengembangan Ekosistem Kekayaan Intelektual - Sihotang, Kortini JM (Universitas Pahlawan Tuanku Tambusai, 2025)
The development of an intellectual property (KI) ecosystem is very important to support the progress of innovation and protection of intellectual property rights in Indonesia. As an institution that has the authority to formulate policies and supervise the implementation of laws related to IP, the Ministry of Law and Human Rights plays a role in creating a conducive environment for the development of research, industry and creativity. Collaborative governance built between the government, private sector, academics and society focuses on aligning policies, increasing awareness of the importance of IP protection, and utilizing information technology to facilitate access and management of intellectual property rights. Through these efforts, it is hoped that a dynamic IP ecosystem will be created that supports global competitiveness, as well as providing benefits for national economic development. The challenges faced include the uneven distribution of information, as well as the need to adjust regulations that are responsive to technological and industrial developments. Therefore, synergy between various parties, under the coordination of the Ministry of Law and Human Rights, is the key to realizing an effective and inclusive IP ecosystem.